Evaluation of water-land resources in karst regions within the framework of sustainable development goals - Zhang, Hao; Zhou, Qingping; Yang, Jianzan; Xiang, Huawei (Frontiers in Environmental Science, 2025)
IntroductionThe shortage and irrational utilization of water-land resources (WLR) are the main obstacles to the sustainable development of karst regions.MethodsIn accordance with the principles of Sustainable Development Goals (SDGs), an evaluation system for WLR utilization was established. As a representative karst region in China, Guizhou Province was selected to analyze the spatio-temporal variation characteristics of the sustainable development level of WLR from 2000 to 2020, and then revealed the driving factors by using factor detector.ResultsThe key findings are as follows: 1) There was a slight intensification in the bearing pressure of cultivated land and water resources, whereas the stress on construction land underwent a notable reduction, from 9.71 in 2000 to 2.02 in 2020, and the pressure on ecological land experienced a modest alleviation. 2) The matching degree of WLR increased significantly at the provincial and prefecture-level city scales, but the effectiveness of improvement at the county scale was limited. 3) The sustainable development level exhibited an upward trajectory, but the sustainable development potential index remained relatively low, consistently below 0.3. 4) Factors urbanization rate and NDVI exerted a pronounced influence on the spatial differentiation of sustainable development level, with the synergistic driving effect of factors sharing the same attribute significantly heightened.DiscussionRecommendations include urbanization construction, strengthening the control of rocky desertification, improving water conservancy infrastructure, and establishing cross-regional cooperation mechanisms for cultivated land and ecological land protection to boost the overall sustainable resources utilization in karst regions.